2014
DOI: 10.1155/2014/102404
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanofabrication by Atomic Force Microscopy-Based Mechanical Processing

Abstract: This paper reviews silicon nanofabrication processes using atomic force microscopy (AFM). In particular, it summarizes recent results obtained in our research group regarding AFM-based silicon nanofabrication through mechanochemical local oxidation by diamond tip sliding, as well as mechanical, electrical, and electromechanical processing using an electrically conductive diamond tip. Microscopic three-dimensional manufacturing mainly relies on etching, deposition, and lithography. Therefore, a special emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…However, when chemical methods are mixed with mechanical processes, precision can be extended to the atomic scale because the mechanical energy can be used to activate chemical reactions [38]. A recent study performed by Chen et al [6] revealed that a single atomic layer of Si can be removed via a mechanochemical method, which was theoretically verified using molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when chemical methods are mixed with mechanical processes, precision can be extended to the atomic scale because the mechanical energy can be used to activate chemical reactions [38]. A recent study performed by Chen et al [6] revealed that a single atomic layer of Si can be removed via a mechanochemical method, which was theoretically verified using molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Attaining single atomic layer removal is the goal that every researcher in this field is aiming at, even though much progress is needed to achieve this reliably. Different methods and perspectives are being approached by the researchers, such as mechanical [34,37,38], mechanochemical [6,39,40], and electrochemical [41,42], to perfectly remove an atomic layer from a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility of AFMs and their unique abilities to investigate sample surfaces in air, vacuum and liquid environments have led to the development of a large number of operating modes, such as contact, semi-contact and non-contact modes [1], [2]. These developments have paved the way for substantial advancement in a variety of fields since the invention of AFM in the 1980's [3], including in biological and life sciences [4]- [6], semiconductor metrology and manufacturing [7]- [9], nanofabrication [10]- [12], and high-density data storage systems [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel nanoprobes are used as a way to overcome this constraint, boosting its productivity [11][12][13][14]. Atomic force microscope (AFM), scanning tunneling microscope (STM), and scanning near-field optical microscope (SNOM) are among the apparatus which can be modified and used in SPL techniques [15][16][17][18][19]. Patterning with atomic resolution of about 1Å has been predicted by AFM [1].…”
Section: Introductionmentioning
confidence: 99%